MANAJEMEN PENGEMBANGAN KURIKULUM BERBASIS KKNI - FATHONI, AHMAD (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2015)
KKNI embodies the quality and identity of the Indonesian nation associated with national education and training system is owned by Indonesia. (Presidential Decree No. 8 of 2012). In KKNI perspective, every program of study is required to clarify the "profile of graduates' expected through tracking studies, feasibility studies and analysis of the needs in the community. Based curriculum development KKNI namely to help, understand, and control the implementation of the curriculum, so that educational institutions can be cooperatively and independently identify curriculum requirements with the principle of (1) productivity, (2) Democratization (3) Cooperative, effectiveness and efficiency, (4) Direct the vision, mission and objectives set out in the curriculum.